2023
DOI: 10.2196/45143
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality and Impact of eHealth Tools: Systematic Literature Review and Narrative Synthesis

Abstract: Background Technological advancements have opened the path for many technology providers to easily develop and introduce eHealth tools to the public. The use of these tools is increasingly recognized as a critical quality driver in health care; however, choosing a quality tool from the myriad of tools available for a specific health need does not come without challenges. Objective This review aimed to systematically investigate the literature to underst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 109 publications
0
32
0
Order By: Relevance
“…The overviewed studies collectively contribute to a nuanced understanding of the evolving landscape of digital health interventions with a focus on technology assessment, although not always very markedly [ 17 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. They emphasize the critical importance of systematically technologically assessing eHealth tools [ 28 ], considering TA stakeholder preferences [ 29 ], and recognizing the broader impact on well-being [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overviewed studies collectively contribute to a nuanced understanding of the evolving landscape of digital health interventions with a focus on technology assessment, although not always very markedly [ 17 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. They emphasize the critical importance of systematically technologically assessing eHealth tools [ 28 ], considering TA stakeholder preferences [ 29 ], and recognizing the broader impact on well-being [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The overviewed studies collectively contribute to a nuanced understanding of the evolving landscape of digital health interventions with a focus on technology assessment, although not always very markedly [ 17 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. They emphasize the critical importance of systematically technologically assessing eHealth tools [ 28 ], considering TA stakeholder preferences [ 29 ], and recognizing the broader impact on well-being [ 30 ]. Specific evaluations of TA in some domains, such as the effectiveness of telehealth-based cancer rehabilitation [ 31 ] and the integration of tools for peer-to-peer interactions in digital interventions for psychotic disorders [ 40 ], shed light on targeted healthcare areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Narrative synthesis was used to analyze the interview transcripts, using NVivo (QSR International), a computer-assisted qualitative data analysis software. Data coding began with a preliminary data extraction grid that included themes based on the expert comments received in the Round 1 survey and informed by our previous work that aggregated the factors impacting adoption from patients' and clinicians' perspectives, as well as the initial list of criteria for eHealth assessment [20,[54][55][56]. More codes were added as they emerged during the analytical process.…”
Section: Between Rounds Expert Interviewsmentioning
confidence: 99%
“…Their study identified the key elements influencing an efficient e-health policy framework and discovered a gap in the context of developing nations, and proposed a fourstep e-health policy implementation guideline for effective e-health implementation in the context of developing countries. A review conducted by Jacob et al [41] added to the expanding body of research that explored the standards used to evaluate the effectiveness and implications of e-health tools. It proved that different frameworks are employed in different ways to evaluate the effectiveness and value of e-health solutions.…”
Section: Literature Reviewmentioning
confidence: 99%